Measuring Wasting and Stunting Prevalence Among Children Under 5 Years of Age and Associated Risk Factors in Papua New Guinea: New Evidence From the Comprehensive Health and Epidemiological Surveillance System - Pham, Bang Nguyen; Silas, Vinson D.; Okely, Anthony D.; Pomat, William (Frontiers in Nutrition, 2021)
Background: Papua New Guinea (PNG) has undergone a significant health transition, with the prevalence of non-communicable diseases increasing. Many children under 5 years of age suffer from the burden of malnutrition. While wasting and stunting still remain high, children who are overweight and obese are reportedly increasing. Objective: This study reports the prevalence of wasting, stunting, underweight, and overweight children under five in PNG and explores potential household and maternal socioeconomic factors associated with malnutrition. Method: Data were drawn from the Comprehensive Health and Epidemiological Surveillance System (CHESS) in PNG. Height and weight were directly measured, and wasting, stunting, overweight, and underweight statistics were determined using the 2006 WHO Standard Growth Standards. Household and maternal factors were assessed with parent interviews conducted by trained data collectors. Multivariate logistic regression analyses were conducted to report associations between selected socioeconomic correlates and child malnutrition outcomes. Result: The prevalence of wasting, stunting, underweight, and overweight children was 13.8, 46.5, 18.2, and 18%, respectively. Children from households with food shortage were more likely to be wasted than those from households without such an experience [OR: 1.43 (95% CI: 0.93–2.21)]. Children from the poor quintile were more likely to be stunted than those from the richest quintile [OR: 1.2 (95% CI: 0.79–1.82)]. Other factors associated with wasting included living in an urban vs. rural area [OR: 1.36 (0.77–2.4)], middle household wealth quintile vs. richest quintile [OR: 0.77 (0.38–1.55)], mothers in union with a man vs. mother unmarried or live in union [OR: 0.76 (0.4–1.42)], and male children vs. female [OR: 0.77 (0.53–1.11)]. Factors associated with stunting included residing in urban vs. rural areas [OR: 1.13 (0.8–1.6)], mother in union vs. single mother [OR: 0.86 (0.59–1.24)], and mothers with preparatory/elementary vs. mothers with vocational/college education [OR: 0.15 (0.02–1.01)]. Conclusion: An integrated approach is needed to comprehensively address the household socioeconomic factors at the household level, contributing to the improvement of child health and development in PNG.